Implicit and Explicit Auditory Modulation on Perceptual Decision in Vision - Kohske Takahashi; Katsumi Watanabe (i-Perception, 2011)
Given ambiguity in visual inputs, human chooses one among diverse possible interpretation. Perceptual decision in visual competition is susceptible to inputs into the modalities other than vision. Here we will review recent investigation conducted in our laboratory. The studies mainly aimed to examine how auditory inputs implicitly and/or explicitly affect temporal characteristics of perceptual decision. Here is the summary of our findings: (1) Synchronization: perceptual alternation for bi-stable visual patterns can be synchronized with implicit auditory events after experiencing synchronized audio-visual event. (2) Destabilization: auditory transients immediately collapse current percepts of bi-stable visual patterns. (3) Suppression/restoration: auditory transients immediately reveal and/or conceal masked visual patterns in continuous flash suppression. These results would imply that temporal patterns of perceptual decision in vision might be, implicitly and explicitly, related to other sensory modalities.